(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study of newspaper headlines is given in the article. The definition of headlines is learned. Functional features of headlines are defined. It substantiates the need of researching the newspaper headlines on the semantic-structural and stylistic aspect in the Karakalpak linguistics